Public Service and Micro-Small Enterprise Developments in Indonesia - Metasari Kartika (Integrated Journal of Business and Economics (IJBE), 2019)
This study aims to analyze the influence of public service on the Micro-Small Enterprise (MSE) developments in Indonesia. The study method used was regression analysis panel data with fixed effect approach; because of the limited data availability, the data was only taken from 2013-2015. The study findings show that public service and education projected by gross participation data have a positive influence on the development of MSE, while the economic growth and minimum wage policy have a negative influence on the development of MSE in Indonesia. Based on those findings, this study concludes that the public service in the form of government spending allocation policy, especially on the service and economic functions, will stimulate the increase of MSE numbers.